Os efeitos de uma intervenção psicoterápica breve junguiana em um grupo de portadores de doença periodontal - Greghi, Mônica Perri Kohl (2009)
The objective of this study was to analyze the effects of a brief Jungian psychotherapeutic intervention for a group of individuals suffering from periodontal disease. A total of 26 subjects were selected, male and female, aged between 30 and 60. The subjects were randomly divided between an experimental group (N=13) and a control group (N=13). The experimental group experienced a psychotherapeutic process, which consisted of 14 weekly sessions, of one and a half hours each. The two groups were evaluated with respect to the level of cortisol saliva, level of stress and periodontal conditions, before and after the experimental period. The results identified improvements in the experimental group, that were statistically significant, with respect to the levels of cortisol saliva (NC), the levels of stress and evidence of plaque (IP) gingivitis (IG), which measure, respectively, the accumulation of bacterium plaque and gum inflammation. The control group, which did not undergo a psychotherapeutic process, reported a statistically significant worsening in the plaque levels (IP), with no statistically significant alterations in the other indices. Descriptions and qualitative analyses were made of some thematic categories from the psychotherapeutic sessions, highlighting, amongst others, the difficulty of verbal assertive expression by the subjects. Interpretations and symbolic interpretations were made of the mouth and speech. Non verbal expressive techniques and symbolic amplification provided the transduction of the organic symptom to the abstract expression of the complex, which resulted in improvements in the periodontal disease. The results identified the need to consider the use of psychotherapy as an integral part of treating periodontal disease